The role of electronic auditing in the detection of fraud and accounting error the case study of the Bank of Khartoum for the period from 2008 to 2018 - ABDEL-MAGEED, RUGAIA AAMIR (Journal of Economic, Administrative and Legal Sciences, 2019)
This study dealt with the electronic review and its statement in reducing fraud and accounting errors, as well as clarifying how to reduce the chances of committing mistakes and fraud to establish controls and procedures that prevent this, the study of the case of Bank of Khartoum. The problem of the study in the proper role of electronic auditing in reducing fraud and accounting errors, as well as in ignorance of accounting principles and assumptions and the non-use of electronic technology in accounting, which can help to a large extent in reducing fraud and accounting errors and the introduction of electronic technology in the review process. The study followed the historical approach through reviewing the previous studies as well as the inductive method and analytical descriptive approach using the statistical packages of social sciences (SPSS) to achieve the objectives of the study. The study data were collected by questionnaire distributed to the branches of Bank of Khartoum in the capital, and reached a number of results, the most important of which is the existence of an effective system of electronic auditing leads to the discovery of fraud and errors. There is no statistically significant relationship between the effective internal audit system and the degree of fraud and errors detected by the auditor. And that the examination and evaluation of the internal control system has a positive impact on the process of electronic auditing and effectiveness in detecting fraud and accounting error in the bank. Through the results of the study, the researcher reached a number of recommendations, including the need to apply the electronic review because it helps the auditor to expand the sample size, which enhances confidence in his neutral opinion in the financial statements.
Keywords: internal audit; external audit; accounting operations; error detection